BULLYING BEHAVIOR AMONG TEENAGERS AT JUNIOR HIGH SCHOOL LAMPUNG -INDONESIA - Teguh Pribadi; Susri Utami; Marliyana Marliyana (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Cases of bullying in schools are common at this time. In Junior High School (Sekolah Menengah Pertama 2 Muhammadiyah) Bandar Lampung in 2017 has 16 cases of bullying behavior or about 15% of cases.Purpose: Knowing Factors Associated With Bullying Behavior of Junior High School (Sekolah Menengah Pertama 2 Muhammadiyah) Bandar Lampung Year 2018.Methods: Quantitative research using cross sectional. The participant was 109 students as respondents (total sampling) and obtained 92 respondents as suitable of inclusion criteria. Univariate data analysis to know the frequency distribution and bivariate analysis using chi-square test.Results: In this study showed the frequency distribution of respondents had low self esteem 38 (84.6%) behaved bullying, poor family care pattern 44 (88%) bullying behavior, 39 poor peers 39 (79,6%) bullying behavior. the relationship between bullying behavior and self-esteem (p value 0,000), bullying behavior and family parenting (p value 0,000), bullying behavior and peers group (p value 0,000).Conclusion: There is a relationship between factors (self esteem, family parenting, and peers) with bullying behavior among students of Junior High School (Sekolah Menengah Pertama 2 Muhammadiyah) Bandar Lampung 2018. Suggest to the highest Education Department of Bandar Lampung, especially through Counseling department to be conducted another research in another school and follow up on the results of this study as: doing school programs that creating networks support, sports, consultants, art, community and anti-bullying campaigns.